Kant on the Jews and their Religion (Diametros, 2020)
The main focus of the article is the analysis of Kant’s notion of Judaism and his attitude toward the Jewish nation in a new context. Kant’s views on the Jewish religion are juxtaposed with those of Mendelssohn and Spinoza in order to emphasize several interesting features of Kant’s political and religious thought. In particular, the analysis shows that, unlike Mendelssohn, Kant did not consider tolerance to be the last word of the enlightened state in matters of its coexistence with religion. The author also argues that Kant’s fascination with Mendelssohn’s Jerusalem was premature and that his later disappointment with Mendelssohn’s persistent adherence to Jewish orthodoxy reflects his understanding of the condition of Judaism in the context of the new era of Enlightenment. Moreover, the paper addresses in a novel way the relevant connections between Kant and Spinoza, showing substantive similarities between their notions of Judaism and Christianity, and provides an overview of Kant’s historical involvement with Jewish issues, which are significant given the argumentative structure of the article.
Keywords: Kant; Mendelssohn; Spinoza; Judaism; Christianity; state-church separation thesis; religious pluralism; Enlightenment; Haskalah